THE ROLE OF DATA IN STRATEGIC DECISION MAKING: BIG DATA AS A COMPETITIVENESS TOOL - Antônio Scapini, Lucas (Revista Gênero e Interdisciplinaridade, 2025)
The current context of organizations is marked by increasing data availability and the need to turn it into strategic insights for more assertive decisions. In this scenario, tools such as Business Intelligence (BI) and Enterprise Resources Planning (ERP) emerge as essential resources to optimize processes and anticipate market trends. This study aimed to analyze the role of strategic use of data in planning and making organizational decisions, highlighting the relevance of these technologies for business competitiveness. The relevance of the theme is the need for companies to adapt to a dynamic environment, where the ability to interpret large volumes of information can determine their success or obsolescence. The methodology adopted was qualitative, based on bibliographic survey of studies published between 2021 and 2023, focusing on articles that addressed the impact of data analysis tools on organizational strategies. The results indicate that a data -oriented strategy, when supported by robust and integrated technological tools, promotes greater operational efficiency, innovation and sustainability. In addition, it is emphasized the importance of an internal cultural change to maximize the potential of these technologies. It is concluded that strategic use of data is an indispensable competitive differential for modern organizations.